Batch fluidized bed reactor based modified biosynthetic crystals: Optimization of adsorptive properties and application in fluoride removal from groundwater. (October 2021) - Wang, Zhao; Ali, Amjad; Su, Junfeng; Hu, Xiaofen; Zhang, Ruijie; Yang, Wenshuo; Wu, Zizhen
Abstract: A batch fluidized bed reactor (BFBR) with modified biosynthetic crystals (MBC), derived from Pseudomonas sp. HXF1, was investigated for the treatment of the groundwater containing fluoride (F − ). Impacts of different hydraulic retention time (HRT), pH, and initial F − concentration on F − removal were examined and the maximum defluorination efficiency was recorded as 95.20%. Moreover, recycling experiments were performed to evaluate the stability of repeated use. BFBR/MBC system showed a long-term effective treatment outcome with low fluctuation in the concentrations of residual Ca 2+ and F − . The formed precipitates were characterized by SEM, XPS, XRD, and FTIR. The defluorination mechanisms of BFBR/MBC system were defined as the chemisorption and induced crystallization of Ca5 (PO4 )3 F on the MBC surface. As a feasible, economical, and environment-friendly technique, the method has a long-term value, which suggests promising applications in F − removal and resourceful treatment. Graphical abstract: Image 1 Highlights: A batch fluidized bed reactor was developed with modified biosynthetic crystals. Under the optimum conditions, fluoride (F − ) removal reached to 95.20%. Residual Ca 2+ and F − remained below 120 and 0.4 mg L −1 after 42 cycles. F − removal occurred simultaneously by both coprecipitation and adsorption.